(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2023)
The current regulatory framework regarding equality and non-discrimination based on gender is the result, among other factors, of a long, complex and unfinished process of conceptualization of the human rights of women and LGTB people, in the feminist and legal jurisprudence approaches. Based on the fundamental postulates of feminist and transfeminist legal feminist theories, as an expression of the demands for justice and search for answers to the violations of women’s human rights of women, the article reviews the regulatory framework of gender equality and non-discrimination in our country and makes a general assessment of the situation through the uninterrupted forty years of democracy.